Role of Pneumonectomy in T1–4N2M0 Non-Small Cell Lung Cancer: A Propensity Score Matching Analysis - Wang, Suyu; Wang, Qing; Zhu, Wanli; Wei, Juan; Feng, Di; Lv, Xin; Liu, Meiyun (Frontiers in Oncology, 2022)
Background: The eighth edition American Joint Committee on Cancer (AJCC) N2 stage disease constitutes approximately 20%–30% of all non-small cell lung cancer (NSCLC). Concurrently, surgery remains the first-choice treatment for patients with N2 NSCLC if feasible. However, the role of pneumonectomy in N2 NSCLC has rarely been investigated and remains controversial. Methods: We enrolled 26,798 patients with T1–4N2M0 NSCLC (stage IIIA/IIIB) from the Surveillance, Epidemiology, and End Results (SEER) database between 2004 and 2015. We compared the overall survival (OS) and cancer-specific survival (CSS) between patients who received pneumonectomy and those who didn't receive surgery. The Kaplan–Meier method, Cox regression analyses, and propensity score matching (PSM) were applied to demonstrate the effect of pneumonectomy. Results: Patients receiving pneumonectomy had a significantly better OS and CSS than those without pneumonectomy both before [adjusted-HR (95%CI): 0.461 (0.425–0.501) for OS, 0.444 (0.406–0.485) for CSS] and after PSM [adjusted-HR (95%CI): 0.499 (0.445–0.560) for OS, 0.457 (0.405–0.517) for CSS] with all P values <0.001. Subgroup analysis demonstrated concordant results stratified by demographic or clinicopathological variables. In sensitivity analysis, no significant difference was observed between patients receiving single pneumonectomy and chemoradiotherapy without surgery in OS and CSS both before [unadjusted-HR (95%CI): 1.016 (0.878–1.176) for OS, 0.934 (0.794–1.099) for CSS P=0.832] and after PSM [unadjusted-HR (95%CI): 0.988 (0.799–1.222) for OS, 0.938 (0.744–1.182) for CSS] with all P values >0.4. Conclusion: For patients with T1–4N2M0 NSCLC (stage IIIA/IIIB), pneumonectomy is an independent protective factor of OS and should be considered when applicable.